(3cJGH aj GdCOhjIs ((3TMGOg GdMcje s)
(3ChdgG (B:s
(3EYde Cf GdCOhjI HYVgG fHGJjI hHYVgG eYOfjI hHYVgG MjhGfjI hGdeYOfjI CaVdgG eG cGf ef GdeYGOf GdeYQaI HgG s
(3BNQgG (B:s
(3bGd YHO Gddg Hf LHQjd ai eSNfGJg ef WHGFY GdMjhGf hNhGUgG bO LQH gPG hjbGd GdScQ MOkG Ke hGdMeO ddg Ydi GdCaVGd s
(3HgG fXGe GdJYbjHIs
(3HBNQgG ahGFO WHjIs
(3JGQjN fSNgG SfI (B1758 (3es
(3JMJhi Ydi hUaGJ WHjI hWQjbI JMVjQgG s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdWHs